2016
DOI: 10.3758/s13421-016-0622-y
|View full text |Cite
|
Sign up to set email alerts
|

The limited use of the fluency heuristic: Converging evidence across different procedures

Abstract: In paired comparisons based on which of two objects has the larger criterion value, decision makers could use the subjectively experienced difference in retrieval fluency of the objects as a cue. According to the fluency heuristic (FH) theory, decision makers use fluency-as indexed by recognition speed-as the only cue for pairs of recognized objects, and infer that the object retrieved more speedily has the larger criterion value (ignoring all other cues and information). Model-based analyses, however, have pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The fluency heuristic, in contrast, is silent about the predicted effect size for knowledge cases as compared with recognition cases. Notably, this MSH prediction has already found some support in previous research (e.g., Hilbig et al, 2011;Marewski & Schooler, 2011;Pohl et al, 2016;Schwikert & Curran, 2014).…”
Section: Recognition Memory In the Context Of The Rhsupporting
confidence: 80%
See 1 more Smart Citation
“…The fluency heuristic, in contrast, is silent about the predicted effect size for knowledge cases as compared with recognition cases. Notably, this MSH prediction has already found some support in previous research (e.g., Hilbig et al, 2011;Marewski & Schooler, 2011;Pohl et al, 2016;Schwikert & Curran, 2014).…”
Section: Recognition Memory In the Context Of The Rhsupporting
confidence: 80%
“…In this paper, we primarily aim to test a crucial and counterintuitive prediction that has not been directly addressed before and conflicts with the popular notion that processing fluency -or cognitive fluency in general -boosts preference for a choice option (Schooler & Hertwig, 2005;Zajonc, 1968). In addition, we provide support for the MSH through conceptual replications of predictions previously tested by different researchers (Erdfelder et al, 2011;Hertwig, Herzog, Schooler, & Reimer, 2008;Hilbig, Erdfelder, & Pohl, 2011;Schooler & Hertwig, 2005;Pohl, Erdfelder, Michalkiewicz, Castela, & Hilbig, 2016). In this way, we aim at closing a gap in previous research on the MSH and provide converging evidence on the importance of memory strength (rather than recognition judgments) in recognition-based decision making.…”
Section: Introductionmentioning
confidence: 89%
“…The fluency heuristic states that the faster recognized item is chosen in trials involving two recognized objects (RR pairs; Hertwig et al, 2008; Schooler & Hertwig, 2005). Despite empirical evidence against such an account (Hilbig, Erdfelder, & Pohl, 2011; Pohl, Erdfelder, Michalkiewicz, Castela, & Hilbig, 2016), the recognition speed could still confound any analysis of choice RTs. Specifically, memory-based decisions in trials with further knowledge might not be faster because of the increased coherence of further information with recognition (as stated by PCS) but rather due to faster recognition itself (Gigerenzer & Goldstein, 2011).…”
Section: The Recognition Processmentioning
confidence: 99%
“…2 Although a previous study showed that the use of the fluency heuristic was independent from the order of recognition and choice tasks (Pohl, Erdfelder, Michalkiewicz, Castela, & Hilbig, 2016), we used the first ratings only. This was to ensure that prior exposure to the items had no influence on choice (in line with exposure effects; e.g., Zajonc, 1968 For the fictitious-fictitious (FF) pairs, there is no criterion to judge which one is the larger city, but participants may falsely recognize a city and choose accordingly.…”
Section: Correct Respondingmentioning
confidence: 99%